2013
DOI: 10.1007/s00267-013-0029-5
|View full text |Cite
|
Sign up to set email alerts
|

Chlorophyll a Simulation in a Lake Ecosystem Using a Model with Wavelet Analysis and Artificial Neural Network

Abstract: Accurate and reliable forecasting is important for the sustainable management of ecosystems. Chlorophyll a (Chl a) simulation and forecasting can provide early warning information and enable managers to make appropriate decisions for protecting lake ecosystems. In this study, we proposed a method for Chl a simulation in a lake that coupled the wavelet analysis and the artificial neural networks (WA-ANN). The proposed method had the advantage of data preprocessing, which reduced noise and managed nonstationary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 31 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Partly because of a large amount of natural evapotranspiration and artificial water withdrawal, its ecological environment is fragile. In particular, the recent construction of dams and reservoirs upstream of the lake, which are intended to provide economic and social benefits to water users, has profoundly changed the natural hydrologic regime 22 , 39 . Low water use efficiency and ecological degradation will hinder the implementation of the plan of establishing XNA.…”
Section: Introductionmentioning
confidence: 99%
“…Partly because of a large amount of natural evapotranspiration and artificial water withdrawal, its ecological environment is fragile. In particular, the recent construction of dams and reservoirs upstream of the lake, which are intended to provide economic and social benefits to water users, has profoundly changed the natural hydrologic regime 22 , 39 . Low water use efficiency and ecological degradation will hinder the implementation of the plan of establishing XNA.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for using CHL-a and transparency is their wide application as indicators of the eutrophication and turbidity in aquatic ecosystems [6][7][8][9][10]. The accurate simulation and prediction of chlorophyll-a concentrations have become an important issue as it is considered to be a central metric for reservoirs eutrophication management [11]. In addition, transparency (Secchi depth) provides an estimate of the volume of the habitat of phytoplankton and the extent of the benthic habitat of primary productivity as well as turbidity [10,12,13].…”
mentioning
confidence: 99%
“…Polat [13] demonstrated that the concentration of NO NO N, PO P, and SiO Si in surface water could significantly affect nutrient and Chl concentration. Wang et al [14] took 14 variables, including hydrological, meteorological, and physicochemical data, into account to simulate the Chl concentration in Lake Baiyangdian using wavelet analysis and an artificial neural network. It is noted that all these studies were based on a relatively long period of several years during which the data were gathered monthly.…”
Section: Introductionmentioning
confidence: 99%